2020
DOI: 10.3390/f11030361
|View full text |Cite
|
Sign up to set email alerts
|

Increased Drought Sensitivity Results in a Declining Tree Growth of Pinus latteri in Northeastern Thailand

Abstract: Climate change may lead to alterations in tree growth and carbon cycling. Interpreting the response of forest growth to climate change requires an understanding of the temporal and spatial patterns of seasonal climatic influences on the growth of tree species. However, the effects of climate change on pine forest dynamics in tropical region of Thailand remain poorly understood. This study develops three new tree ring-width chronologies of Pinus latteri (Tenasserim pine) in northern and northeastern Thailand an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
4
11
0
Order By: Relevance
“…Our study revealed that the growth of C. axillaris in the Mo Singto plot had a continually increasing trend early in the analysis period, but that growth rate declined in recent decades, especially after the year 2003. These results were consistent with a previous study in which the growth trend of P. laterri in Thailand had an increasing trend from 1951 to 1984, but a decreasing trend from 1985 to 2017 [54,56]. Growth over time also decreased for four broad-leaved tree species in Thailand [57].…”
Section: Long-term Growth Trends Of Choerospondias Axillarissupporting
confidence: 92%
See 1 more Smart Citation
“…Our study revealed that the growth of C. axillaris in the Mo Singto plot had a continually increasing trend early in the analysis period, but that growth rate declined in recent decades, especially after the year 2003. These results were consistent with a previous study in which the growth trend of P. laterri in Thailand had an increasing trend from 1951 to 1984, but a decreasing trend from 1985 to 2017 [54,56]. Growth over time also decreased for four broad-leaved tree species in Thailand [57].…”
Section: Long-term Growth Trends Of Choerospondias Axillarissupporting
confidence: 92%
“…It is possible that the mean temperature at this site was sufficiently low that evapotranspiration had not induced water deficit. The correlation between tree growth and July-to-October precipitation became stronger in recent years, which was similar to studies on Pinus latteri in Northeastern Thailand [54] and Pinus sylvestris in Poland [55].…”
Section: Growth-climate Relationshipssupporting
confidence: 86%
“…The chronology also had a high positive correlation (p < 0.01) with the current year temperature in October, the present year average temperature, and the previous year average temperature. Rakthai et al (2020) found that the growth of Pinus latteri at three sites had a significantly positive correlation with precipitation, relative humidity, and self-calibrated Palmer Drought Severity Index during the dry season and early rainy season, and significant negative correlation with temperatures (mean, maximum, and minimum) from April to August. Pumijumnong and Palakit (2020) reconstructed a 191-year chronology of Pinus merkusii growing in central Thailand and found that the extreme maximum temperature in April was the main driver inducing intra-annual ring formation.…”
Section: Discussionmentioning
confidence: 88%
“…Dendroclimatologists in Thailand have conducted successful climate reconstruction studies using teak (Tectona grandis) and pine (Pinus spp.) (Pumijumnong and Wanyaphet 2006;Buckley et al 2007;Pumijumnong and Eckstein 2011;Palakit et al 2015Palakit et al , 2016Buajan et al 2016;Muangsong et al 2016Muangsong et al , 2018Lumyai and Duangsathaporn 2017a,b;Preechamart et al 2018;Yordtong et al 2019;Rakthai et al 2020;Buareal et al 2020). They discovered that pine species and variation in teak ring width was related to changes in temperature and rainfall and strong relationship with the regional climate data of the Equatorial Southern Oscillation Index and the Equatorial Sea Surface Temperature.…”
Section: Introductionmentioning
confidence: 99%
“…8 BAI (basal area increment) through time, the smoothing line operated for a 5-year period season rainfall (March-May) (Tiwari et al 2017). The negative impact of temperature-induced drought to pine forest growth has also been reported in different regions of Asia, Pinus taiwanensis, Pinus massoniana in the Dabie Mountains in subtropical China (Cai et al 2020), Pinus koraiensis (Korean pine) of Changbai Mountain in northeast China (Yu et al 2013) and Pinus latteri of Northeastern Thailand (Rakthai et al 2020) all showed decreased growth at lower elevations under climate change characterized by warming and drought. The BAI trend in the study area showed that the chir pine forest was not in good health and is showing poor performance in terms of carbon assimilation.…”
Section: Baimentioning
confidence: 91%